The gravity tree : the true story of a tree that inspired the world - Redding, Anna Crowley (Harper, an imprint of HarperCollins Publishers, 2021)
"Part scientific explanation, part biography, this nonfiction picture book explores the life of the fabled apple tree that inspired Newton's theory of Gravity-from a minor seed to a monumental icon that has inspired the world's greatest minds for over three and a half centuries"--